Management of Oromandibular Dystonia: A Case Report and Literature Update - Suma Gn; Adrita Nag (Case Reports in Dentistry)
Oromandibular dystonia (OMD) is a movement disorder characterized by involuntary, paroxysmal, and patterned muscle contractions of varying severity resulting in sustained spasms of masticatory muscles, affecting the jaws, tongue, face, and pharynx. It is most commonly idiopathic or medication-induced, but peripheral trauma sometimes precedes the condition. We present a case report of a 26-year-old female patient who suffered repetitive bouts of hemifacial muscle contractions for 2 years on closing the mouth which interfered in patient’s well-being and quality of life by hampering her ability to eat and talk and to the extent of inability to breath due to contractions of her neck muscles. Prompt diagnosis of a chronic oromandibular dystonia jaw closing type led to the control of the spasmodic muscle contractions within 24 hours and alleviation of patients fear of morbidity.